2003
DOI: 10.1126/science.1090842
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation-Related Chromatin Remodeling in Activity-Dependent Bdnf Gene Regulation

Abstract: In conjunction with histone modifications, DNA methylation plays critical roles in gene silencing through chromatin remodeling. Changes in DNA methylation perturb neuronal function, and mutations in a methyl-CpG-binding protein, MeCP2, are associated with Rett syndrome. We report that increased synthesis of brain-derived neurotrophic factor (BDNF) in neurons after depolarization correlates with a decrease in CpG methylation within the regulatory region of the Bdnf gene. Moreover, increased Bdnf transcription i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
1,068
4
12

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,316 publications
(1,124 citation statements)
references
References 28 publications
40
1,068
4
12
Order By: Relevance
“…44 On the other hand, BDNF promoter IV binds the transcriptional repressor, MeCP2 (a methyl-CpG-binding domain protein), in complex with the corepressor sin3a and HDACs. [45][46][47] Inhibition of HDAC by VPA or other inhibitors could cause dissociation of the repressor-corepressor complex from the promoter, resulting in transcriptional disinhibition. It is noteworthy that the antidepressant effect of imipramine is largely reversed by HDAC5 overexpression in the hippocampus of mice subjected to chronic defeat stress, which per se induces downregulation of BDNF III and IV mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…44 On the other hand, BDNF promoter IV binds the transcriptional repressor, MeCP2 (a methyl-CpG-binding domain protein), in complex with the corepressor sin3a and HDACs. [45][46][47] Inhibition of HDAC by VPA or other inhibitors could cause dissociation of the repressor-corepressor complex from the promoter, resulting in transcriptional disinhibition. It is noteworthy that the antidepressant effect of imipramine is largely reversed by HDAC5 overexpression in the hippocampus of mice subjected to chronic defeat stress, which per se induces downregulation of BDNF III and IV mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…32 There is therefore an emerging concept for a more gene selective role for MeCP2 involving regulation of a smaller number of key regulatory genes such as brain-derived neurotrophic factor (BDNF), a bona fida MeCP2 target. 33,34 However, this concept does not exclude gene selective or global regulatory functions for MeCP2 in non-neuronal cell types of the fully developed adult. Absence of MeCP2 expression in normal adult human and rodent liver demonstrated in the present study helps to explain the lack of hepatic phenotype for Mecp2 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…345 There are also reports that Mecp2 plays a role in the regulation of Bdnf levels. 134,201,202 Reduction in the levels of Bdnf exacerbates the phenotype of both the Rett syndrome-model mouse 346 and the Sert deletion line. [208][209][210] In the Rett syndrome-model mouse, Bdnf overexpression with an inducible Bdnf transgene leads to partial correction of abnormalities linked to loss of Mecp2 function.…”
Section: Discussionmentioning
confidence: 99%
“…[192][193][194] Work with mouse lines characterized by deficient Bdnf has shown that these trophic effects are important for normal serotonergic neurotransmission. [195][196][197][198][199][200] In addition, several lines of evidence have provided support for a role of Mecp2 in the regulation of activity-dependent transcription of Bdnf, 134,201,202 suggesting that alterations in 5-HT signaling could arise from deficient Mecp2 function, through dysregulation of Bdnf. Bdnf-null mice die soon after birth, but mutants have been developed with conditional disruption of Bdnf, limited to either the prenatal or postnatal period.…”
Section: Autism Candidate Genes and Synaptic Functionmentioning
confidence: 99%